O dzielności, prawości, szczęściu i losie. Dydaktyzm w tragedii rzymskiej czasów republiki - Hartleb-Kropidło, Barbara (Wydawnictwo Naukowe Uniwersytetu im. Adama Mickiewicza, 2009)
The aim of this paper is to present the didactic function of Roman tragedy of the Republic Period, achieved by introducing into the plot of plays various sentences, sayings or expressions intended to advise or recommend a course of conduct.

Roman archaic tragedy is preserved only in fragments. Some of them are derived from the works of grammarians, lexicographers, antiquarians and scholiasts, who explained old Latin words and expressions to their contemporaries. Some of the fragments are handed down by poets and writers of later epochs due to their aesthetic or didactic value. One of them is Cicero, who often enriched his rhetorical or philosophical writings with quotations from Roman drama. Many of them are “short literary forms”, such as sentences, proverbs, maxims or apophthegms, containing such stylistic features as alliteration, parallelism, ellipsis or hyperbole. They often describe a basic rule of conduct or express a general truth or wise observation in a clever way, and sometimes they express a truth based on common sense, generally known. They touch upon themes of fidelity, courage, honesty, morality, moderation, wisdom, patience and justice and show, through the example of mythical heroes, the proper way of living and acting. They are part of philosophical meditation, which enriched Roman plays in a way comprehensible to the Roman audience. This feature undoubtedly has its roots in Greek tragedy. A very interesting problem is how the mythology of Roman gods was set in a political or historical context. When Accius, for instance, deals with moral or political themes, freely using the myths, he touches on problems existing in contemporary Roman society, such as, for example, deep contrasts between political factions or growth of personal power. He also takes part in debates over ideas, which owing to his plays could take place not only among well-educated citizens, but also in all classes of society attending the theatre. In this way Roman tragic poets were ‘teaching the people’, as Varro says (De Lingua Latina 6, 19): togata praetexta ... docuit populum.
About Virtue, Worth, Fortune and Fate. Didacticism in Roman Tragedy
Keywords: Roman tragedy; didacticism; proverb